Validity and Reliability of Development of Self-confidence Assessment Instruments for Students on Chemistry Subject (Journal of Research and Educational Research Evaluation, 2022)
Self-confidence assessment instrument in Chemistry subjects is very necessary, but there is no self-confidence assessment instrument in Chemistry subjects. The purpose of this study was to test the validity and reliability of confidence assessment instruments in Chemistry subjects. The research and development method used in this study is the model of non-test instrument development proposed by Mardapi. The participant is a document and an expert. Data collection using a questionnaire with 10 statements. The research instrument uses a questionnaire with a rating scale of 1 to 5. Data analysis using Aiken's V formula for content validity test with the help of Microsoft Excel and reliability estimation using Intraclass Correlation Coefficients (ICC) for reliability test between rater with the help of SPSS 25. The data of the results showed the value of Aiken's coefficient V on each item of the statement is ≥ 0.3, then it can be said that all aspects are valid. In addition, the estimation of reliability also produces an intraclass correlation coefficients (ICC) value of 0.735, then it can be said that this instrument is quite reliable. Thus, it can be concluded that the confidence assessment instrument in Chemistry subjects has high validity and reliability between rater is quite strong and is expected to be used as a reference for affective domain assessment for students.